Competitive Strategy Formulation for Market Share Growth and Business Sustainability: A Case Study of PT. Mensa - Eko Susanto; Janfry Sihite (Journal of Sustainable Economic and Business, 2026)
Objectives: This study addresses the limited market penetration of PT. Mensa’s Animal Nutrition and Health (ANH) division in Indonesia’s feed-additive distribution market and aims to formulate prioritized competitive strategies to expand market share while strengthening business sustainability. Methodology: A mixed-method approach uses both qualitative interviews with internal managers, sales teams, customers, and expert principals, along with a quantitative analysis of existing data like company sales reports and industry publications. The strategy tools used one after another are Resource-Based View (RBV), Porter’s Five Forces, SWOT , TOWS matrix, and the Quantitative Strategic Planning Matrix (QSPM). Findings: Sustainable advantages derive from supply chain integration, organic portfolios, and formula locking services. High trust and service requirements create significant entry barriers for new competitors. Evaluation reveals a strong internal position with a 3.00 IFAS score and moderate external responsiveness with a 2.75 EFAS score. The Quantitative Strategic Planning Matrix identifies the Total Solution and Technical Intimacy strategy as the optimal choice with a 6.2 attractiveness score. Conclusion: This study identifies market stagnation and risk within the ANH Division due to concentrated sales sources. The research recommends the Total Solution and Technical Intimacy strategy to drive growth through vertical and horizontal integration. This approach builds loyalty in medium and small scale feed mills while enhancing farmer efficiency and supporting Sustainable Development Goals. The resulting framework directs the division toward a 20 percent market share by 2030 to ensure long term business sustainability.